Impacts of people at-risk of either cow milk allergies or lactose intolerance on their daily calcium intake and bone mineral density - Kongpharm, Kornkanok; Nakklay, Parinda; Kongtong, Chunhakan; Tanapumchai, Pichaya; Prapkree, Lukkamol; Rueangsri, Narisa; Singhato, Alongkote (Frontiers in Nutrition, 2024)
Background People who are at risk of either cow milk allergies or lactose intolerance may need to avoid consuming milk and milk products, which are well-known abundant sources of calcium (Ca). This limitation in calcium intake could affect bone health. Currently, there is limited knowledge on the impact of avoiding the consumption of milk and milk products on the daily Ca intake and bone mineral density (BMD) of people at risk of cow milk allergies. This study aimed to investigate the differences between the amount of Ca intake and BMD values between people who are at risk of cow milk allergies and those who are not. Methods A total of 80 participants were recruited, and further divided into two groups, the at-risk cow milk allergies (AR) group (n = 40) and the normal (NOR) group, using the cow milk allergies and lactose intolerance screening questionnaire. The anthropometric assessment, body composition analyses, 3-day dietary record, and bone mass density (wrist and ankle bones) measurement of all participants were collected using the dual x-ray absorptiometry (DEXA) technique to compare the differences of variables between the two groups. Results The participants in the AR group presented a significantly lower amount of Ca intake (317 mg/day) than those in the NOR group (623 mg/day) (p < 0.05). The bone mineral density (BMD) parameters indicated that the NOR group presented significantly higher T-scores and BMD values of the wrist (T-score = −0.27 and BMD = 0.57 g/cm2) and ankle (T-score = −0.01 and BMD = 0.59 g/cm2) bones when compared with the AR group (T-score = −1.96 and BMD = 0.48 g/cm2 for the wrist bone, and T-score = −1.18 and BMD = 0.47 g/cm2 for the ankle bone) (p < 0.05). In addition, the results indicated significantly positive correlations between the amount of Ca intake and the T-scores and BMD values of both the wrist and ankle bones among all participants (p < 0.05). Conclusion In this responding sample, participants at risk of cow milk allergies experienced a significantly negative impact on the amount of Ca intake and BMD values. Professionals in nutrition and dietetics should provide nutrition education and strategies that can enhance the Ca intake among this population to help them meet the daily Ca intake recommendation, ultimately leading to better bone health.